Integrated technology of the surfactants and phytohormones biosynthesis by Nocardia vaccinii IMV B-7405 for their use in crop production - Pirog, Tatiana; Piatetska, Daria; Leonova, Natalia; Shevchuk, Tetiana (My University, 2024)
The strain Nocardia vaccinii IMV B-7405, which produces phytohormones and surfactants, is a promising agent for the development of integrated technologies to obtain complex preparation to be used in crop production. Cultivation of bacteria was carried out in a liquid medium with 2% refined or waste oil and 100–300 mg/l of tryptophan (the precursor of the phytohormone auxin biosynthesis) was added to the medium. The concentration of auxins was determined by the method of high-performance liquid chromatography, surfactants – by weight method. Antimicrobial activity of surfactant was analyzed by the indicator of minimum inhibitory concentration (MIC). Greenhouse experiments were carried out using tomato plants; the number of fruits and their weight were analyzed. Determination of the protective effect of surfactants against bacterial diseases of tomatoes was carried out by the method of separated leaves

Штам Nocardia vaccinii ІМВ В-7405, який продукує фітогормони та ПАР, є перспективним агентом для розробки інтегрованих технологій отримання комплексного препарату для використання в рослинництві. Культивування бактерій проводили в рідкому середовищі з 2% рафінованої або відпрацьованої олії та додаванням 100–300 мг/л триптофану (попередника біосинтезу фітогормону ауксину). Концентрацію ауксинів визначали методом високоефективної рідинної хроматографії, ПАР – ваговим методом. Антимікробну активність сурфактанту аналізували за показником мінімальної інгібуючої концентрації (МІК). Тепличні експерименти проводили з використанням рослин томатів; аналізували кількість плодів та їх вагу. Визначення захисної дії ПАР проти бактеріальних хвороб томатів проводили методом відокремлених листків
Keywords: кафедра біотехнології і мікробіології; Nocardia vaccinii IMB В-7405; auxins; ауксини; surfactants; поверхнево-активні речовини; tomatoes; томати; antibacterial; антибактеріальна активність